Comparison of Foreign Tourists’ Motivation Factors: Does cultural background matter? - Kantabutra, Saranya; Saiprasert, Wanlanai; Chernbumroong, Sainatee; Kowsuvon, Kunsiree (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2019)
The study aims to examine motivation of foreign tourists using “push and pull” motivation factors between tourists from western and Asian countries. A sample of 400 was drawn from foreign tourists who visited Chiang Mai. When considering top-five push and pull factors, the result reveal that some motivation factors exist only in a particular group. For instance, the need to experience local people way of life is among the top-five most important push factors for Western tourists while the need to relax their mind and the need to promote good health, physically and mentally are found in only Asian tourist. In terms of pull factors, natural attraction is found in Western tourists while comfort is found in Asian tourists. Moreover, perceptions of foreign tourists towards some motivation factors are statistically different. For instance, when considering push factors, tourists from western countries place more importance on the need to learn different cultures and to experience local people way of life while Asian tourists are more interested in the need to relax their mind and the need to promote good physical and mental health. For pull factor, Asian tourists give more importance to comfort than their western counterparts. Discussion and management implication are also provided.